Potassium nitrate priming mitigates salt stress on wheat seedlings - Steiner, Fábio (2019)
Seeds of wheat (Triticum aestivum L., cv. Jadeíde 11) were used to investigate the effects of potassium nitrate priming on germination and early seedling growth under salt stress. It was hypothesized that priming with potassium nitrate may improve seed germination and plant establishment by mitigating the negative effects of saline stress through its role in cell osmotic balance. The seeds were soaked in distilled water or in a 10 g L–1 KNO3solution at 25 °C for 2 hours, and after drying, were distributed in plastic boxes with blotter paper containing different salt solutions prepared with concentrations of 0 (control), 25, 50, 75 and 100 mmol L–1 NaCl. The plastic boxes were kept in a seed germinator, at 22 °C for 12 days. A completely randomized design in a 2 × 5 factorial scheme with four replications of 50 seeds each was used. The primed seeds with KNO3 showed improved germination performance, early growth and vigor index of wheat seedlings in salt stress conditions. Low salt concentrations may induce osmotic adjustment activity in the wheat plants and lead to increases in shoot and root length of wheat seedlings, whereas higher concentrations cause severe inhibition of plant growth. The ‶Jadeíde 11″ wheat cultivar is a moderately tolerant genotype to salt stress during the seedling establishment stage by presenting yield stability index greater than 0.74 until the level of 100 mmol L–1 of NaCl, and therefore can be recommended for cropping in soils with high salinity levels.